Gender: Psychological perspectives - Brannon, Linda (Routledge, 2017)
"Gender: Psychological Perspectives" synthesizes the latest research on gender to help students think critically about the differences between research findings and stereotypes, provoking them to examine and revise their own preconceptions. The text examines the behavioral, biological, and social contexts in which women and men express gendered behaviors. The text's unique pedagogical program helps students understand the portrayal of gender in the media and the application of gender research in the real world. -- From publisher's description. Contenu : Preface -- Acknowledgements -- About the author -- The study of gender -- Researching sex and gender -- Gender stereotypes: masculinity and femininity -- Hormones and chromosomes -- Theories of gender development -- Developing gender identity -- Intelligence and cognitive abilities -- Emotion -- Relationships -- Sexuality -- School -- Careers and work -- Health and fitness -- Stress, coping, and psychopathology -- Treatment for mental disorders -- How different? -- References -- Index.
Keywords: approches et analyses; biologie; comportements sexuels; cours; différence des sexes; discipline; discours dominant; identité sexuelle; maternité; paternité; premier cycle; psy4910; psychologie; relations amoureuses; santé; santé mentale; sciences; sciences humaines; sexisme; sexualité; stéréotypes de genre; systèmes d'oppressions; thématiques; violences; violences sexuelles; études de genres

The Cyborg Embryo: Our Path to Transbiology - Franklin, S. (THEORY CULTURE AND SOCIETY, 2006)
It is useful on the occasion of the 21st anniversary of the ‘Cyborg Manifesto’ not only to reconsider its lessons in the context of what is frequently described as the re-engineering of ‘life itself’, but to look at Haraway’s earlier work on embryos. In this article I begin with Haraway’s analysis of embryology in the 1970s to suggest her cyborg embryo was already there, and has, if anything, gained relevance in today’s embryo-strewn society. I argue further, as the title suggests, that the cyborg embryo has been crucial in defining our path to what I am calling here, building on Haraway’s notion of trans from Modest_Witness, ‘transbiology’ - broadly meaning stem cell research, cloning, tissue engineering and regenerative medicine. To illustrate this argument I draw on recent ethnographic fieldwork in a new stem cell derivation facility in the UK built adjacent to an IVF surgery. Using this example, I explore the important and paradoxical role of IVF in the emergence of stem cell science, cloning and transbiology, suggesting that Haraway’s analysis remains crucial to understanding the ironic and contradictory, and unexpectedly generative, circumstances through which the IVF-stem cell interface - the door to transbiology - came into being.
Keywords: approches et analyses; biologie; care; corps; cours; discipline; discours dominant; fecondation in vitro; féminisme cyborg; justice reproductive; lit4700; maternité; premier cycle; ressource en ligne; santé; sciences; sciences humaines; sociologie; systèmes d'oppressions; thématiques